Effectiveness of MURDER Learning Strategy on Analytical Thinking Ability of SMK DARMA Plus Solokuro Lamongan Students (SCHOOLAR: Social and Literature Study in Education, 2022)
The purpose of this study is to know the effectiveness of MURDER learning strategy on students' analytical thinking skills and to know the difference between students who are taught and those who are not taught using MURDER learning strategies in Jawahirul Kalamiyah class X smk DARMA Plus Solokuro Lamongan subjects. This research is an experimental study using the design form of One-Group Pretest-Postest Design. The population in this study was grade X students consisting of two classes, namely class X TKJ and class X Automotive. Sampling techniques in this study using saturated sampling techniques that are all members of the population sampled by 38 students. Based on the results of statistical analysis can be known that, the application of murder learning strategies can improve the thinking ability of students' analysis. The results of spss output version 26 using the Mann-Whitney U test showed a significant value of 0.000 < 0.05 so it can be said that there is an influence of murder learning strategy on students' analytical thinking ability. Then H0 was rejected and H1 was accepted.